(untitled) (Anclajes, 2012)
In 1982, El Establo cooperative created Teatro del Bajo in Neuquén. From that moment on, the Rio Negro newspaper spread and legitimized the action of the theatre group under a section called “Culture and Entertainment¨. The corpus analyzed in this article includes all the notes about Teatro del Bajo published in the mentioned paper between 1982 and 1983, in the months before and during the democratic transition period. Some interviews to actors and actresses who were part of Teatro del Bajo are added to complement the analysis. The objective is to determine what representations of Teatro del Bajo were spread by the Río Negro newspaper, and how they affected the readers’ imagination in the cultural context that cities in the Alto Valle (an Argentine region that covers the East of Neuquén Province and the North-West of Río Negro Province) experienced during the years under study.